(untitled) (LTU Journal of Advanced Computing & Engineering, 2026)
A prime example of utilizing traditional mud-based housing systems is to gain knowledge on sustainable, climate-sensitive, and culturally inclined ways of constructing houses. The paper includes a critical examination of the ancient methods of Tharu mud houses in Kanchanpur, Nepal, in terms of their applicability on the global and national systems of vernacular architecture and sustainable building. Based on the global research on earthen construction technologies, e.g., adobe, cob, rammed earth and wattle-and-daub, and various Nepalese traditions, the review appraises Tharu houses within the framework of the essential sustainability indicators, e.g., environmental footprint, thermal comfort, cost/efficiency, and socio-cultural meaning. Tharu mud houses consist of locally available materials, including mud, bamboo, straw, and timber which indicate that they have low embodied energy, carbon footprint, and also effective passive design strategies that can fit the hot-humid Terai climate. Thick earthen walls, shaded verandas, and natural ventilation are among the features that promote the achievement of stable indoor thermal conditions without involving the consumption of mechanical energy. Nevertheless, the available literature gives huge gaps in quantitative evaluation, especially to the methods of thermal performance, lifetime cost evaluation, and structural behavior during environmental risks. The proposal identifies that a multi-dimensional assessment is most effective and possibly that the combination of indigenous Tharu construction expertise and modern sustainability systems would generate resilient and low-carbon residential approaches to housing in the rural and peri-urban areas of Nepal.